Note—Effects of Substituting a Linear Goal for a Fractional Goal in the Goal Programming Problem - Hannan, Edward L. (Management Science, 1977)
In a recent article in Management Science, Awerbuch et al. [Awerbuch, S., J. G. Ecker, W. A. Wallace. 1976. A note: hidden nonlinearities in the application of goal programming. Management Sci. 22 (8, April) 918–920] discuss the occurrence of nonlinearities in the application of goal programming and conclude that direct linearization may not be possible when goal constraints are of a fractional nature.